What is Fox News? Partisan Journalism, Misinformation, and the Problem of Classification. (March 2022) - Bauer, A.J.; Nadler, Anthony; Nelson, Jacob L.
Fox News is one of the most popular news sources in the United States. Yet, there are those who reject the idea that Fox should be considered a news source in the first place, claiming it should be considered something more akin to propaganda. This article uses the ambiguity surrounding Fox News' classification as an opportunity to explore how news sources get defined and categorized within journalism research and practice. It discusses three approaches that can be utilized to understand and categorize partisan media—producer-focused, audience-focused, and critical/normative. It explores the benefits and limitations of these perspectives and the need for scholarly inquiry that transverses and synthesizes them. We argue that an increasingly variegated news landscape calls for scholars to develop a richer vocabulary for distinguishing key features of partisan news outlets and greater reflexivity in research design that acknowledges the challenges inherent in translating meaning and values between producers, audiences, and scholars.